Sustainable Plantation Forestry Problems, Challenges and Solutions - Hidayat, Herman (Springer Singapore, 2018)
This book discusses sustainable forest management from the perspectives of sociology, anthropology, politics, economics and policy. It examines the roles of governments, private sectors, NGOs, academics and local communities in implementing sustainable plantation forestry, which aims to supply timber for the forestry industry while at the same time reducing global warming. The book also explores the debates on sustainable forest management practices in several countries, and examines the effects of political ecology on plantation forestry as well as the impact of climate change and conservation programs. By analyzing a number of interrelated issues, it offers a valuable resource for all governments, private companies, practitioners, NGOs, academics and students studying forest management and political ecology from a social sciences perspective.